Political Institutions and Their Historical Dynamics - Sandberg, Mikael (Public Library of Science, 2012)
Traditionally, political scientists define political institutions deductively. This approach may prevent from discovery of existing institutions beyond the definitions. Here, a principal component analysis was used for an inductive extraction of dimensions in Polity IV data on the political institutions of all nations in the world the last two centuries. Three dimensions of institutions were revealed: core institutions of democracy, oligarchy, and despotism. We show that, historically and on a world scale, the dominance of the core institutions of despotism has first been replaced by a dominance of the core institutions of oligarchy, which in turn is now being followed by an increasing dominance by the core institutions of democracy. Nations do not take steps from despotic, to oligarchic and then to democratic institutions, however. Rather, nations hosting the core democracy institutions have succeeded in historically avoiding both the core institutions of despotism and those of oligarchy. On the other hand, some nations have not been influenced by any of these dimensions, while new institutional combinations are increasingly influencing others. We show that the extracted institutional dimensions do not correspond to the Polity scores for autocracy, “anocracy” and democracy, suggesting that changes in regime types occur at one level, while institutional dynamics work on another. Political regime types in that sense seem “canalized”, i.e., underlying institutional architectures can and do vary, but to a considerable extent independently of regime types and their transitions. The inductive approach adds to the deductive regime type studies in that it produces results in line with modern studies of cultural evolution and memetic institutionalism in which institutions are the units of observation, not the nations that acts as host for them.